Assessment of stormwater runoff management practices and governance under climate change and urbanization: An analysis of Bangkok, Hanoi and Tokyo. Issue 64 (October 2016) - Saraswat, Chitresh; Kumar, Pankaj; Mishra, Binaya Kumar
Highlights: Paper explore the review of stormwater runoff management practices to achieve urban water security. Study based on comparative review of policies and strategies adopted by Tokyo, Bangkok and Hanoi. Study analyse the abilities of stormwater run-off management policies to achieve water resiliency. Paper provides commentary for policy makers to design optimal runoff capture measures and policies. Analyse the role of technologies to establish adaptation strategies for water cycle restore. Abstract: As human history is changing on many fronts, it is appropriate for us to understand the different perspectives of major global challenges, of which, water is a major priority. The water resources in urban areas are either approaching or exceeding the limits of sustainable use at alarming rates. Groundwater table depletion and increasing flood events can be easily realized in rapidly developing urban areas. It is necessary to improve existing water management systems for high-quality water and reduced hydro-meteorological disasters, while preserving our natural/pristine environment in a sustainable manner. This can be achieved through optimal collection, infiltration and storage of stormwater. Stormwater runoff is rainfall that flows over the ground surface; large volumes of water are swiftly transported to local water bodies and can cause flooding, coastal erosion, and can carry many different pollutants that are found on paved surfaces. Sustainable stormwater management is desired, and the optimal capture measure is explored in the paper. This study provides commentary to assist policy makers and researchers in the field of stormwater management planning to understand the significance and role of remote sensing and GIS in designing optimal capture measures under the threat of future extreme events and climate change. Community attitudes, which are influenced by a range of factors, including knowledge of urban water problem, are also considered. In this paper, we present an assessment of stormwater runoff management practices to achieve urban water security. For this purpose, we explored different characteristics of stormwater runoff management policies and strategies adopted by Japan, Vietnam and Thailand. This study analyses the abilities of Japanese, Vietnamese and Thai stormwater runoff management policies and measures to manage water scarcity and achieve water resiliency. This paper presents an overview of stormwater runoff management to guide future optimal stormwater runoff measures and management policies within the governance structure. Additionally, the effects of different onsite facilities, including those for water harvesting, reuse, ponds and infiltration, are explored to establish adaptation strategies that restore water cycle and reduce climate change-induced flood and water scarcity on a catchment scale.